Effectiveness of Ketepeng Cina (Cassia alata Linn.) Leaf Powder as an Active Ingredient in Antiseptic Liquid Soap - Encik Eko Rifkowaty; Adha Panca Wardanu; Kendri Wahyuni (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study aimed to evaluate the effectiveness of Cassia alata Linn. (ketepeng Cina) leaf powder as an active ingredient in virgin coconut oil (VCO)-based antiseptic liquid soap. A Completely Randomized Design (CRD) was employed with three treatments consisting of 2 g, 4 g, and 6 g of leaf powder (b/v). The evaluated parameters included total flavonoid content, phytochemical screening, functional group analysis using FTIR, LC-MS, pH, specific gravity, viscosity, free alkali, foam stability, unsaponifiable fraction, and inhibition zones against Escherichia coli and Malassezia furfur. The results indicated that increasing concentrations of ketepeng leaf powder positively correlated with total flavonoid levels and significantly enhanced the inhibition zone against E. coli, but showed no notable activity against M. furfur. Phytochemical analysis confirmed the presence of flavonoids and steroids in the powder, while liquid soap formulations contained flavonoids and saponins. FTIR analysis further verified flavonoid compounds, whereas LC-MS identified lauric Acid (m/z 274) and quercetin (m/z 303), contributing to antimicrobial activity. Statistical analysis (ANOVA, alpha = 0.05) showed no significant effect of leaf powder addition on pH, free alkali, unsaponifiable fraction, viscosity, specific gravity, or foam stability. The formulated liquid soap complied with the Indonesian National Standard (SNI 06-4085-1996) for pH and free alkali, ensuring safety for consumer use. Overall, ketepeng cina leaf powder demonstrated potential as a natural antimicrobial agent in herbal antiseptic liquid soap formulations.